Neonatal respiratory outcomes in pregnancy induced hypertension: introducing a novel index. (16th February 2020) - Razak, Abdul; Patel, Waseemoddin; Durrani, Naveed; McDonald, Sarah D.; Vanniyasingam, Thuva; Thabane, Lehana; Shah, Prakesh S.; Mukerji, Amit
Abstract: Objective: To evaluate short-term respiratory outcomes, mortality and bronchopulmonary dysplasia (BPD) in preterm infants born to mothers with and without pregnancy induced hypertension (PIH). Methods: Exposed infants <33 weeks' gestation were matched to controls in a 1:2 ratio, based on gestation, sex and antenatal steroid exposure in this retrospective cohort study. Primary outcomes were a novel cumulative respiratory index (cRI) (product of mean airway pressure-hours and FiO2 -hours while on invasive ventilation during first 72 hours), mortality and BPD. Results: Seventy-nine exposed infants were matched with 158 controls. cRI was higher in exposed infants (median 1854; IQR 186–13, 901) versus controls (median 1359; IQR 210–11, 302) but not statistically significant ( p  = .63). On conditional regression analysis, PIH did not predict cRI (adjusted β  = 0.96; 95% CI = 0.79–1.17; p  = .712). No association between PIH and mortality (unadjusted odds ratio [OR] = 3.14; 95% CI = 0.76–13.0; p =.11) was identified. PIH was significantly associated with BPD on univariate analysis (OR = 2.29; 95% CI = 1.02–5.17; p =.046), but not after adjustment (aOR = 1.26; 95% CI = 0.38–4.19; p =.7). Conclusions: PIH was not associated with cRI, mortality or BPD in this study. Further validation of cRI and exploration of its relationship with PIH as well as neonatal outcomes is warranted.